Figurative Language in the Poetry Anthology Meracik Kenangan: Structural Study of Poetry: Bahasa Figuratif dalam Antologi Puisi Meracik Kenangan: Kajian Struktural Puisi - Sri Utami Rizki; Sendang Mulyono (Universitas Negeri Semarang, 2025)
This article discusses the use of figurative language in the poetry anthology “Meracik Kenangan”. The background of this study focuses on the importance of figurative language in enriching the language and meaning of poetry, as well as how figurative language can increase emotional appeal for readers. The method used in this study is qualitative analysis, where each poem is analyzed using a structural approach to identify and classify the types of figurative language contained in it. The results of the analysis show that there are five dominant types of figurative language, namely simile, hyperbole, personification, metaphor, and repetition. The use of figurative language in the poetry anthology “Meracik Kenangan” not only enriches the language, but also provides emotional depth and deeper meaning for readers. This study can provide new insights into literary techniques in poetry and highlight the importance of figurative language as a key element in creating meaningful and interesting literary works. Artikel ini membahas tentang penggunaan bahasa kiasan dalam antologi puisi “Meracik Kenangan”. Latar belakang penelitian ini berfokus pada pentingnya bahasa kiasan dalam memperkaya bahasa dan makna puisi, serta bagaimana bahasa kiasan dapat meningkatkan daya tarik emosional bagi pembaca. Metode yang digunakan dalam penelitian ini adalah analisis kualitatif, di mana setiap puisi dianalisis menggunakan pendekatan struktural untuk mengidentifikasi dan mengklasifikasikan jenis bahasa kiasan yang terkandung di dalamnya. Hasil analisis menunjukkan bahwa ada lima jenis bahasa kiasan yang dominan, yaitu simile, hiperbola, personifikasi, metafora, dan repetisi. Penggunaan bahasa kiasan dalam antologi puisi “Meracik Kenangan” tidak hanya memperkaya bahasa, tetapi juga memberikan kedalaman emosional dan makna yang lebih dalam bagi pembaca. Penelitian ini dapat memberikan wawasan baru tentang teknik sastra dalam puisi dan menyoroti pentingnya bahasa kiasan sebagai elemen kunci dalam menciptakan karya sastra yang bermakna dan menarik.